How Political Signals Affect Public Support for Judicial Nominations: Evidence from a Conjoint Experiment. (June 2017) - Sen, Maya
How do Americans evaluate potential US Supreme Court candidates? Using a novel, two-part conjoint experiment, I show that respondents put high importance on the political leanings of potential Court candidates, a finding in contrast with the scholarly view that the public views the Court as different from other, more political institutions. Indeed, when respondents are given information about a nominee's partisan leanings, they rely extensively on that information in deciding whether to support the candidate, whether they trust the candidate, and whether they find the candidate qualified. By contrast, when partisan information is withheld, respondents appear to use other kinds of signals, such as race, to fill in the gaps. Those who are most knowledgeable about the Court are most influenced by these partisan signals, providing further support for the importance of political heuristics. The results suggest that the public's evaluation of judicial nominees is more in line with how it evaluates other political actors. They also suggest that even candidates with excellent qualifications need not garner bipartisan public support.